The Essence of Legislation in Realizing a Legal State Based on Justice and Welfare - Anshar, Sayid; Netrivianti, Netrivianti (Jurnal Ilmiah Ekotrans & Erudisi, 2024)
This research examines the essence of legislation in realizing a legal state that focuses on justice and people's welfare. The rule of law is a fundamental basis for achieving justice and prosperity. Legislation, as the main instrument of the rule of law, is central to translating the values of justice and welfare into concrete practice. This research explores the definition and characteristics of the rule of law and the crucial role of legislation in upholding the supremacy of law, creating legal certainty, and realizing justice and prosperity for all people. Furthermore, this research identifies fundamental principles that must be realized in legislation to achieve justice and prosperity, such as, Rule of law and legal certainty, Justice and equality before the law, Benefit and welfare of the people, Accountability and transparency and Community participation in drafting legislation. This research also discusses challenges and solutions in realizing just and prosperous legislation. Factors that hinder the realization of just and prosperous legislation are analyzed, and efforts to overcome these challenges are proposed.